Corneal surgery : essential techniques - Zuberbuhler, Bruno (Springer Berlin Heidelberg, 2013)
This book is an informative and comprehensive guide to the essential techniques currently employed in corneal surgery. It focuses in particular on two principal areas: the treatment of corneal disorders by means of different forms of corneal transplantation and the use of the Excimer laser to treat refractive disorders.   In order to facilitate learning and later deployment of the techniques a multimedia approach is used. Surgical steps are described clearly within the book and can then be observed in detail on the accompanying high-quality DVD. A further feature is the inclusion of a chapter devoted to wet lab training, which presents practical preparatory exercises that can be performed by the surgeon, in some cases at home.   This book will be of particular value as a handy reference for ophthalmologists who are just embarking upon their surgical training. However, it will also be informative for trained eye surgeons, who will be able to compare their own practice with the presented procedures and to assimilate the latest techniques.